Edukasi Keterampilan dan Bahasa Melalui Program Sosialisasi Kehidupan Mahasiswa di Dayah Terpadu Al-Muslimun Lhoksukon, Aceh Utara - Nurlaela, Della; Meitriana, Dina; Cahayani, Ica (Jurnal Malikussaleh Mengabdi, 2025)
This Community Service Program was carried out with a crucial objective: to enhance non-technical academic readiness, mastery of functional language, and adaptability among students—particularly final-year students of Madrasah Aliyah (MA) at Dayah Terpadu Al-Muslimun Lhoksukon, North Aceh—in facing the transition to higher education and the increasingly complex world of work. Referring to the Ministry of Education and Culture Regulation (Permendikbud) No. 23 of 2015 on the Cultivation of Character, the effort to foster character education as a collective movement involving the government and society, including higher education institutions, serves as the main foundation of this program. The activity was conducted at Dayah Terpadu Al-Muslimun Lhoksukon on September 13–14, 2025, involving 50 final-year Madrasah Aliyah students. The applied methodology adopted an experiential learning approach through interactive workshops, practical simulations, and comprehensive socialization sessions—distinct from traditional teaching methods. Program evaluation using a descriptive qualitative approach demonstrated a positive and significant impact, assessed through active participation observation, verbal response analysis, and the quality of essays produced. The findings revealed the students’ growing interest in the importance of pursuing higher education, their increasing awareness of personal interests and confidence in oral communication (particularly in English), as well as their awareness of managing personal finances digitally. This activity is expected to strengthen the culture of literacy and readiness of Dayah students in facing future challenges, including becoming university students. Keywords: language skills, santri, university life socialization.